Implementing eco-social policies: Barriers and opportunities. A preliminary comparative analysis - Diletta Carmi (United Nations Research Institute for Social Development (UNRISD), 2016)
Despite the global consensus on the importance of shifting to a model of sustainable development, identifying pathways that can simultaneously and equally fulfil social, economic and environmental goals remains extremely arduous. This paper analyses opportunities for and barriers to the effective adoption of eco-social policies in national programmes by undertaking a comparative analysis of three case studies: Payment for Ecosystem Services in Costa Rica, the Ishpingo-Tambococha-Tiputin (ITT) proposal for Yasuní National Park in Ecuador and the Virunga Alliance in the Democratic Republic of Congo. The three programmes had varying degrees of success. The Payment for Ecosystem Services was a successful national programme that led to unprecedented forest recovery in Costa Rica. On the contrary, the ITT proposal for the Yasuní National Park was a governmental policy initiative that failed due to various national and international issues. The promising Virunga Alliance, a development project implemented in Virunga Park is at risk due to regional insecurity and a fragile national economy. The author looks at the different approaches taken in each country, analysing the benefits and trade-offs as well as the factors that led to their adoption or defeat. She then examines how the actors involved, the economic agenda, the national and international contexts, and the national policy framework influenced the success or failure of ecosocial policies. Drawing from this, she identifies topics for future research on the topic. At the time of writing, Diletta Carmi was working as a Civil Servant at LVIA (Lay Volunteers International Association) in Burkina Faso, dealing with communication, coordination and research for a project on food security.
Keywords: 330